Vlastnosti cementových kompozitů ztužených vlákny z plastového odpadu - Novák J.; Horáková A. (Česká betonářská společnost ČSSI, 2019)
Recyklace odpadu umožňuje určité snížení dopadů na životní prostředí z hlediska globálního oteplování a změny klimatu, spotřeby surovin a energie, produkce odpadů a celkového znečištění životního prostředí. Skutečnost, že Čína v nedávné době omezila dovoz plastového odpadu, vyvolala zájem vědecké komunity o výzkum v oblasti uplatnění tohoto odpadu. V betonovém stavitelství se plastový odpad využívá pro výrobu ztraceného bednění, rozptýlené výztuže a substituci přírodního kameniva a pojiva na cementové bázi. Prezentovaný článek shrnuje základní poznatky o chování a vlastnostech cementových kompozitů ztužených vlákny z plastového odpadu. Pro výrobu cementových kompozitů se zejména využívají polyetylentereftalátová (PET) vlákna získaná z plastových lahví. Ztužení cementového kompozitu vlákny tohoto typu může vést k nežádoucí degradaci způsobené hydrolýzou PET v zásaditém prostředí struktury cementového kompozitu. Z hlediska krátkodobého chování však lze konstatovat, že chování a vlastnosti cementových kompozitů ztužených vlákny z plastového odpadu odpovídají vláknobetonům se syntetickými vlákny z primárních surovin. Konečné vlastnosti čerstvé směsi a výsledného kompozitu se však odvíjí od množství a typu zastoupených vláken.

Recycling of waste enables to reduce the negative impact on the environment in terms of global warming and climate change, raw materials and energy consumption, waste production and possible environmental pollution. The fact, that China has limited the import of plastic waste, results in the interest of the scientific community in research into the application of this waste. In the concrete industry, plastic waste is used for the production of permanent formwork, fibrous reinforcement and as replacement for natural aggregate and cement-based binders. The presented paper summarizes fundamental findings about the beahviour of cement-based composites reinforced with plastic-waste fibers. Mostly, polyethylene terephthalate PET fibers of waste plastic bottles are used for cement-based composites. However the use of these fibers can lead to the PET hydrolysis in the alkaline environment in cementitious composite structure. Short-term behaviour and properties of plastic-waste fiber reinforced concrete correspond to those of conventional synthetic fibre reinforced concrete. However, final properties of a cementitious composite depend on a fiber content and fiber geometry.
Properties of cement-based composites reinforced with plastic-waste fibers
Keywords: Cement-based composite; Plastic waste; Fibrous reinforcement; fibre reinforced concrete; PET